Real-World Therapy Management and Outcomes of First-Line Axitinib Plus Pembrolizumab in Patients With Advanced Renal Cell Carcinoma in the United States - Zakharia, Yousef; Thomaidou, Despina; Li, Benjamin; Siu, Gordon; Levin, Rebecca; Vlahiotis, Anna; Rao, Dharanija; Zanotti, Giovanni (Frontiers in Oncology, 2022)
Background: Combination axitinib plus pembrolizumab is a standard of care in the first-line treatment of patients with advanced clear cell renal cell carcinoma (RCC). This analysis describes the clinical characteristics, treatment management and outcomes of patients receiving first-line (1L) axitinib plus pembrolizumab in a real-world US setting. Methods: Electronic health record (EHR)-derived data from the Flatiron Health Database, which includes ~280 cancer clinics across 800 sites in the US, were used. Patients had confirmed Stage IV or metastatic RCC and initiated 1L axitinib plus pembrolizumab on or after 1/1/2018 to 3/31/2021. Outcomes were best overall response rate; real-world progression-free survival (rwPFS) and overall survival (OS) at landmark time periods (3, 6, 9, and 12 months). Therapy management (TM) included dose hold, dose change and discontinuation. Data are reported as medians (IQR) unless otherwise noted. Results: 355 patients received 1L axitinib plus pembrolizumab, with median follow-up of 9.7 (0.1–24.3) months. IMDC Risk Score was favorable, intermediate, and poor in 27 (7.6%), 126 (35.5%), and 76 (21.4%) patients, respectively (23.4% intermediate/poor, 12.1% unknown). 270 patients (76.1%) received only 1L axitinib plus pembrolizumab and 85 patients (24.3%) received ≥1 subsequent line of treatment; cabozantinib was the most frequent subsequent line of treatment (47.9%). rwPFS at 3 months and 1 year was 77.2% and 39.3%, respectively. OS ranged from 90.8% at 3 months to 73.5% at 1 year. Best overall response rate was 47.9%. Toxicity was the most common reason for first TM events of dose hold, change and discontinuation at, 58.6%, 58.5%, and 45.8%, respectively. Over 80% of patients with TM were able to continue with 1L axitinib plus pembrolizumab. Conclusions: In a real-world setting, axitinib plus pembrolizumab was effective as a 1L treatment for patients with advanced RCC. Dose holds, changes and discontinuation were driven by treatment-related toxicity. Dose holds may represent an effective TM strategy to toxicity.